2015
DOI: 10.1007/s12275-015-3662-2
|View full text |Cite
|
Sign up to set email alerts
|

Statistical experimental design optimization of rhamsan gum production by Sphingomonas sp. CGMCC 6833

Abstract: Rhamsan gum is a type of water-soluble exopolysaccharide produced by species of Sphingomonas bacteria. The optimal fermentation medium for rhamsan gum production by Sphingomonas sp. CGMCC 6833 was explored definition. Single-factor experiments indicate that glucose, soybean meal, K(2)HPO(4) and MnSO(4) compose the optimal medium along with and initial pH 7.5. To discover ideal cultural conditions for rhamsan gum production in a shake flask culture, response surface methodology was employed, from which the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Examples of commercial bacterial polysaccharides include xanthan gum, gellan gum, fucogel, hyaluronic acid and welan gum. Others, with either none or low commercial expression have been reported, for example colanic acid [8], clavan [9] and rhamsan [10]. Beyond the solution properties, they may also present interesting biological activities, namely those composed of l-fucose, l-rhamnose or uronic acids residues.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of commercial bacterial polysaccharides include xanthan gum, gellan gum, fucogel, hyaluronic acid and welan gum. Others, with either none or low commercial expression have been reported, for example colanic acid [8], clavan [9] and rhamsan [10]. Beyond the solution properties, they may also present interesting biological activities, namely those composed of l-fucose, l-rhamnose or uronic acids residues.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon source is both one major constituent for the building of cellular materials and an energy source for polysaccharide synthesis; therefore, it has a significant influence on the synthesis of EPSs . In this study, the effects of 14 different carbon sources including monosaccharides and sugar alcohols (fructose, mannitol, sorbitol, xylose, arabinose, glucose, and galactose), disaccharides (maltose, lactose, and cellobiose), trisaccharide (raffinose) and polysaccharides (glucan T5, starch, and cellulose) at a concentration of 40 g L −1 were investigated (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…It has been reported that Sphingomonas sp. CGMCC 6833 and Sphingomonas sanxanigenes strain NX02 optimally metabolize glucose as their carbon source to produce rhamsan gum and the sphingan Ss . Different from the Sphingomonas sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most-used polysaccharides are xanthan and guar gum. However, there are some new ones that have recently attracted much attention, such as welan and rhamsan gums [5][6][7].…”
Section: Introductionmentioning
confidence: 99%